SARS‐CoV‐2 antibody kinetics in blood donors with a previously positive SARS‐CoV‐2 antibody test within a seroprevalence survey - Levring, Mette B.; Holm, Dorte K.; Nilsson, Anna C.; Bauer, Joschka M.; Jensen, Iben S.; Davidsen, Jesper R.; Rasmussen, Line D.; Sprogøe, Ulrik; Lillevang, Søren T. (Journal of medical virology, 2022)
The persistence of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) antibodies is a matter of importance regarding the coronavirus disease 19 (COVID‐19) pandemic. To observe antibody dynamics, 105 blood donors, positive for SARS‐CoV‐2 antibodies by a lateral flow test within a seroprevalence study, were included in this study. Thirty‐nine (37%) of 105 the donors were confirmed positive by a total Ig Wantai enzyme‐linked immunosorbent assay (ELISA). Three (8%) in this group of 39 reported severe and 26/39 (67%) mild to moderate COVID‐19 symptoms. By further ELISA‐testing, 33/39 (85%) donors were initially positive for IgG antibodies, 31/39 (79%) for IgA, and 32/39 (82%) for IgM, while 27/39 (69%) were positive for all three isotypes. Persistence of IgG, IgA, and IgM was observed in 73%, 79%, and 32% of donors, respectively, after 6–9 months of observation. For IgM antibodies, the decline in the proportion of positive donors was statistically significant (p = 0.002) during 12 months observation, for IgG only the decline at 3 months was statistically significant (p = 0.042). Four donors exhibited notable increases in antibody levels. In conclusion, persistent SARS‐CoV‐2 IgA antibodies and IgG antibodies at 6–9 months are present in approximately three of four individuals with previous mild to moderate COVID‐19.